1984
DOI: 10.1002/hep.1840040514
|View full text |Cite
|
Sign up to set email alerts
|

Sclerotherapy of Esophageal Varices: An Endoscopic and Portographic Study

Abstract: A prospective series of 26 patients with portal hypertension and recent bleeding from esophageal varices was investigated with percutaneous transhepatic selective portography (PTP). PTP was performed immediately prior to and, in 23 patients, just after the initial endoscopic injection sclerotherapy (ST) session to study the acute effects of ST on the mediastinal portal-systemic collaterals. Late follow-up PTP was performed after a median of 8 months in 21 of 26 patients considered endoscopically to be free fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…It has also been reported that the recurrence rate is lower among patients whose treatment includes esophageal transection and devascularization than those without devascularization (32 ). Conversely, Soderlund et al (20) suggested that the selective eradication of submucosal varices, leaving the periesophagdparaesophageal collaterals unaffected, were the mechanism counteracting variceal recurrence after EIS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has also been reported that the recurrence rate is lower among patients whose treatment includes esophageal transection and devascularization than those without devascularization (32 ). Conversely, Soderlund et al (20) suggested that the selective eradication of submucosal varices, leaving the periesophagdparaesophageal collaterals unaffected, were the mechanism counteracting variceal recurrence after EIS.…”
Section: Discussionmentioning
confidence: 99%
“…There still remains some confusion on terminology of collateral veins around the esophagus in patients with portal hypertension. Using percutaneous transhepatic portography, Soderlund et al delineated two parts of collateralsnamely, periesophageal and paraesophageal varicesaround the lower esophagus (20). Periesophageal varices are situated in the connective tissue surrounding the esophagus, whereas paraesophageal varices are mediastinal veins running longitudinally distant to or overlying the esophagus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vessels feeding the esophageal varices have been recognized to be important for recurrence after EIS as well as occurrence of esophageal varices before EIS in patients with portal hypertension. Soderlund et al 17 . reported that selective elimination of submucosal varices without embolization of the periesophageal and paraesophageal collaterals resulted in a higher recurrence rate of varices.…”
Section: Usefulness Of Eus For the Treatment Of Esophageal Varicesmentioning
confidence: 99%